Third Harmonic Model for Salient-Pole Synchronous Generator During Three-Phase to Ground Fault - SHAH RIMAN, NUR IYLIA (2018)
Salient-pole synchronous generator is known as one of third harmonic sources. An event of three-phase to ground fault in an electrical network creates a lowest zero sequence impedance path for the third harmonic current to flow. This fault cause high third harmonic current flowing in neutral line and consequently creates many problems to the system.